Joint Digital Storytelling on Twitter: Creative Appropriation in Political Deliberation - Thimm, Caja J.; Einspänner, Jessica; Dang-Anh, Mark (AoIR Selected Papers of Internet Research, 2013)
Abstract: This paper explores on the basis of empirical research, how patterns of interaction and argumentation in political discourse on Twitter evolve as translocal communities in the creative shape of “joint digital storytelling”. Joint storytelling embraces coordinated activities by multiple actors focusing on a shared topic. By adding personal information and evaluation, participants construct an open narrative format, which can be inviting and inspiring for others, who then join in with their own narratives. This model will be exemplified by analyzing a large amount of tweets (107,000) collected during a political conflict between proponents and adversaries of a local traffic project in Germany. Analysis is based on (1) the textual level, (2) the operative level (hashtags, @- and RT-Symbol, hyperlinks etc.) and (3) the visual level of storytelling (embedded photos, videos). Results show a new way of creating translocal online communities and political deliberation.